Outage and Throughput Analysis of Cooperative Non-Orthogonal Multiple Access based SWIPT Cognitive Relay Network - Abdul Ali Khan; Punithavathi M. Thirunavakkarasu; Nawaf Waqas (International Journal of Technology)
This paper examines the performance of a half-duplex wireless sensor network (WSN) by using cooperative non-orthogonal multiple access (NOMA) integrated with simultaneous wireless information and power transfer (SWIPT) over Rayleigh fading channel to improve the performance of far and cognitive users in terms of spectrum efficiency, prolonging the coverage area, and network lifetime. Two distinct scenarios: one where a direct link exists between the source node S and the far user F, and another one where communication relies on an indirect path incorporating relay node N between node S and F. A new cooperative NOMA based SWIPT cognitive relay protocol is proposed, where a primary user S transmits a composite signal containing information of a near N and far user F, N which acts as an energy harvesting relay first apply NOMA to decode far user information to get its own information The remaining power is harvested by the relay node, and this harvested power is used to transmit information to both the far and cognitive users, respectively. The outage probabilities and throughputs are calculated. Simulated results show that the outage probability of far users with relay and direct link is reduced when compared with N after 25 dB SNR. This, in turn, improves the data rate of far/cell edge users.